EFFECTS OF WEIGHT LIFTING ON MUSCULAR POWER OF FEMALES - Nebojša Čokorilo; Milena Mikalački (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Physical non-activity and bad life style are common among young people nowadays, and they cause many problems with which female could meet. Fitness clbus have unique possibility to ensure time, staff and space for physical activity of young people, and in that way help the promotion of their health. The status of dynamometric power of upper and lower extremities and torso. On the sample of 52 female students aged between 20 and 24. All tests showed statisticaly significiant effect in final measurement compared to initial measurement, after a eight week training treatment.